The Teaching Factory Model and Learning Motivation for the Entrepreneurial Spirit of Vocational High School Students - Atiqoh, Atiqoh; Gunawan, Wawan (LPPM Universitas PGRI Argopuro Jember, 2024)
Teaching Factory has the goal of making students aware that teaching students should be more than just what is in the book. Students not only practice soft skills in learning, learn to work in teams, practice interpersonal communication skills, but also get hands-on experience and work training to enter the world of work later. The purpose of this study was to examine the effect of the Teaching Factory model and learning motivation on the entrepreneurial spirit of SMK students. This study adopted a 2X2 factorial quasi-experimental design. Research data were collected using questionnaire and test methods. The data were then analyzed using the two-way ANOVA statistical analysis technique. The subjects of the study include all students in Class 9 of Junior High School 1 in Situ Azo. The instruments used in this study were the Learning Motivation Questionnaire and the Entrepreneurial Learning Performance Test. The questionnaire used a Likert scale. Commonly used data collection methods in research include: tests, interviews, questionnaires, and observations. Through research, the following results were obtained: (1) There are differences in the impact of the direct guidance teaching factory model on students' entrepreneurship; (2) There are differences in the entrepreneurship among highly educated students. Students with low learning motivation and motivation and (3) There was the interaction between the Teaching Factory model and learning motivation on the entrepreneurial spirit. Based on the results of this study, it was concluded that by using the Teaching Factory model and learning motivation, students' entrepreneurial spirit could be increased. The implication of this research is that the Teaching Factory model can be used as a way to increase students' entrepreneurial spirit.